Differential-Drive Wheeled Robot Controller using Pulse-Width modulation in disinfectant sprayer robot - Yogiswara; Riskiawan, H Y; Anwar, Saiful; Ardiansyah, R (Food and Agricultural Sciences : Polije Proceedings Series, 2020)
This paper describes dc motor control in disinfectant spraying robots using Pulse Width Modulation (PWM) applied to Koesnadi hospital in Bondowoso, East Java as a tool to help sterilize hospital building hallways during the COVID-19 pandemic. Differential drive wheel with caster wheel combination. The robot has a size of L x W x H: 40 cm x 40 cm x 120 cm moves at a set speed to get even spraying results, but that speed becomes unstable due to the linearly changing load of the disinfectant tube. Using PWM is expected to produce different robot speeds according to the load conditions carried by the robot. The Arduino Nano microcontroller as the main controller is used to manage pwm signal cycles as a reference for robot speed when performing disinfectant spraying tasks. The application of PWM to the disinfectant atomizer robot is explained by calculating the estimated time and speed with the observation of the reduction of load conditions on the robot.